The Description of Violence among School-Age Children in Yogyakarta - Nina Dwi Lestari; Oktalisa Puspita Arum (Indonesian Contemporary Nursing Journal, 2021)
Introduction: The occurrence of violence to students increases every year. It came from their parents, environment, and the students. The violence types were physical, verbal or emotional, sexual, and economy. There were several consequences from the violence such as disruption of the child psychic, seriously injured, or trauma. Method: This research used quantitative descriptive with cross sectional design. The population in this research was 220 elementary students in Yogyakarta. The sample of this research was 130 samples that was taken used random sampling technique. The criteria of sample were the students who allowed to participate the research with their parents or parents and never diagnose or have no mental illness beforehand. The instrument in this research was a questionnaire about violence overview that was developed by the researcher and had undertaken the validity and reliability tests. The data analysis used descriptive analysis. Result: Mostly, the violence to the students was dominated by female (51.5%) and students in the low economic background (62.3%). There was an occurrence of violence (56.9%) and verbal violence (68.9%) as the common violence. The largest violence location commonly happened at school (93.2%). Conclusion: The violence prevalence was quite large to students and commonly happened at school. Further research about the factors that influenced the occurrence of violence was needed.